(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Bacteria use quorum sensing to coordinate their actions and communicate with one another.The growth and development of plaque are largely dependent on interactions between oral bacteria in humans. A number of mechanisms are involved in these interactions, including physical contact, metabolic exchange, communication via tiny signal molecules, and genetic material exchange.The majority of quorumsensing-controlled operations are ineffective when carried out by a single bacteria operating alone, but they become effective when simultaneously carried out by a large number of cells.Many strategies are being researched to prevent this communication in order to manage bacterial infections.Additionally, quorum sensing is a means of communication for periodontal pathogens. The benefits of interspecies interaction for microorganisms include expanded habitat range, efficient metabolism, increased resistance to host defense, and increased virulence. This typically has a negative impact on the host and is linked to a number of persistent illnesses, which make treatment difficult. Therefore, novel strategies for treating periodontal disease by quorum sensing suppression require investigation.This review focuses on the architectures of chemical communication networks in bacteria, the integration, processing, and transduction of chemical information to regulate gene expression, the mechanisms involved in intra- and interspecies cell-to-cell communication, and the intriguing prospect of prokaryote-eukaryote cross-communication.